1994
DOI: 10.1055/s-2008-1073013
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Spontaneous General Movements in Full-Term Small for Gestational Age and Appropriate for Gestational Age Newborn Infants

Abstract: Quality of spontaneous movements was studied in 15 healthy full-term appropriate for gestational age (AGA) and in 15 full-term small-for gestational age (SGA) newborn infants. All general movements with a minimal duration of 20 seconds were judged on different aspects of movement quality. From the general movements in each group (AGA: n = 106; SGA: n = 187), dominant patterns were isolated. In the AGA Group 3 dominant patterns of general movements were present. In the SGA Group 5 dominant patterns of general m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…'Chaotic' GMs are also frequently observed in infants with growth retardation, but have not been reported in growthretarded foetuses. In term SGA infants, the qualitative assessment of movement patterns reveals an increased incidence of jerky and tremulous movements 32 . In preterm SGA infants, the presence of this abnormal movement type is related to late foetal heart-rate decelerations and ischaemic alterations of the placenta 13 .…”
Section: Relationship Between Quality Of Gms and Obstetric Variablesmentioning
confidence: 99%
“…'Chaotic' GMs are also frequently observed in infants with growth retardation, but have not been reported in growthretarded foetuses. In term SGA infants, the qualitative assessment of movement patterns reveals an increased incidence of jerky and tremulous movements 32 . In preterm SGA infants, the presence of this abnormal movement type is related to late foetal heart-rate decelerations and ischaemic alterations of the placenta 13 .…”
Section: Relationship Between Quality Of Gms and Obstetric Variablesmentioning
confidence: 99%
“…In some studies, newborns with risk factors for developmental abnormalities were included; in others, preterm SGA newborns were selected. Moreover, a variety of developmental characteristics and assessment at different ages were investigated (33) .…”
Section: Discussionmentioning
confidence: 99%
“…Future research should be directed to evaluate other facets, such as quality and frequency of arm movement. Fourth, there are conflicting results in the literature regarding neurodevelopment of infants exposed to intrauterine malnutrition (33) because of the heterogeneity of the groups studied (inclusion of premature newborns), different assessment instruments and the duration of the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…7,[10][11][12][13] Only a few studies in the literature deal with the relationship between general movements and neurodevelopmental outcome in intrauterine growth retardation. 12,[23][24][25][26] A study on intrauterine growth retarded fetuses and infants looked at the general movement quality in the prenatal and postnatal periods and found that when intrauterine growth retardation was uncomplicated, there was no adverse effect on the general movement quality. 26 Postnatally, similar prenatal general movement quality correlated with a normal outcome at 1 year of age.…”
Section: Discussionmentioning
confidence: 99%